Induction of pulmonary antibodies against oxidized lipids in mice exposed to cigarette smoke. Issue 1 (December 2016) - Thayaparan, Danya; Shen, Pamela; Stämpfli, Martin; Morissette, Mathieu
Abstract Background Chronic cigarette smoke exposure is known to activate the adaptive immune system; however, the functional role of these processes is currently unknown. Given the role of oxidized lipids in driving innate inflammatory responses to cigarette smoke, we investigated whether an adaptive immune response against damaged lipids was induced following chronic cigarette smoke exposure. Methods and results Using a well-established mouse model, we showed that cigarette smoke exposure led to a progressive increase in pulmonary antibodies against oxidized low-density lipoprotein (OxLDL). Functionally, we found that intranasal delivery of an antibody against oxidized phosphatidylcholine (anti-OxPC; clone E06) increased lipid and particle uptake by pulmonary macrophages without exacerbating cigarette smoke-induced neutrophilia. We also found that anti-OxPC treatment increased particle uptake following smoking cessation. Finally, the frequency of pulmonary macrophages with internalized particles was increased after prolonged smoke exposure, at which time lung anti-OxPC responses were highest. Conclusions Altogether, this is the first report to demonstrate a non-pathogenic, and possibly protective, function of a newly identified autoantibody induced by chronic cigarette smoke exposure.